Anchoring in Snow, Ice, and Permafrost - Hironaka, M C (1974)
The objective of the study was to identify present techniques, procedures, and equipment being used for anchoring in snow, ice, frozen ground, and permafrost in arctic regions. Anchoring effectiveness depends on the properties of these materials; therefore, it is necessary to identify the properties of these materials in conjunction with the techniques, procedures, and equipment that are used for anchoring in such material. Based on findings, recommendations for future research and development of anchors and systems for use in such materials are offered.